Existence and Uniqueness of Positive Solutions for Discrete Fourth-Order Lidstone Problem with a Parameter - Yanbin Sang; Zhongli Wei; Wei Dong (Advances in Difference Equations, 2010)
This work presents sufficient conditions for the existence and uniqueness of positive solutions for a discrete fourth-order beam equation under Lidstone boundary conditions with a parameter; the iterative sequences yielding approximate solutions are also given. The main tool used is monotone iterative technique.